1639 Adverse Drug Reactions Associated with Ciprofloxacin in Neonates. (October 2012) - Kuruvilla, KA; James, V; Subramani, M; Mathew, B
Abstract : Background: Ciprofloxacin is used in many nurseries in developing countries. Data on drug concentrations and side effects of ciprofloxacin in neonates is limited. Aims: To study adverse drug reactions(ADR) associated with ciprofloxacin in term and preterm neonates and correlate them with drug levels. Design: Babies of 3 gestational age(GA) groups were enrolled: 37 (gp1), 32–36 (gp2) and 28–31(gp3) weeks. Ciprofloxacin was administered twice daily at 10mg/kg/dose IV. Lab parameters were done at baseline, day 3 and day 7, including peak and trough drug levels. Using Naranjo algorithm, babies who developed new symptoms after starting ciprofloxacin were classified into definite, probable, possible or doubtful ADR. Drug levels were correlated with ADR. Results: 165 babies receiving ciprofloxacin were enrolled. Predominant ADR were jaundice(79%), rash(23%), hyponatremia(28%), anaemia(15%) and hypokalemia(5%). Using Naranjo algorithm, ProbableADR were cardiac arrhythmia, mucosal ulceration, renal failure and seizures. PossibleADR were rash, elevated liver enzymes, feed intolerance and leucopenia. ADRs were self-limited and treatable. The mean (SD) trough and peak values of ciprofloxacin for the entire study population was 3.57(1.88) and 11.67 (3.66), respectively. Mean (SD) trough drug levels were gp 1–2.84 (1.54), gp 2–3.80 (1.9), gp 3–4.06 (1.98). GA did not seem to play a significant role in pharmacokinetics. Drug levels higher than mean were seen in babies with rash, leucopenia and elevated LFT. Levels were adequate in babies with HIE, high in babies with NEC and lower in those with RDS. Conclusions: Ciprofloxacin can be considered safe for treating neonates.